2020
DOI: 10.1530/eje-19-0636
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the link between insulin sensitivity and ectopic fat in men of Black African and White European ethnicity

Abstract: Objectives In men of black west African (BAM) and white European (WEM) ethnicity, we aimed to (1) compare adipose tissue, peripheral and hepatic insulin sensitivity and (2) investigate associations between ectopic fat and insulin sensitivity by ethnicity. Design and methods In overweight BAM (n = 21) and WEM (n = 23) with normal glucose tolerance, we performed a two-step hyperinsulinaemic–euglycaemic clamp with infusion of [6,6 2H2]-glucose and [2H5]-glycerol to measure whole body, peripheral, hepatic and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Data on IHL, whole-body and hepatic insulin sensitivity, as previously reported by our group, 26,30 showed that IHL was lower in BA men, while there were no ethnic differences in hepatic insulin sensitivity or whole-body insulin sensitivity by either M value or M/I (included in Table 2 for reference).…”
Section: Ihl and Insulin Sensitivitysupporting
confidence: 63%
See 3 more Smart Citations
“…Data on IHL, whole-body and hepatic insulin sensitivity, as previously reported by our group, 26,30 showed that IHL was lower in BA men, while there were no ethnic differences in hepatic insulin sensitivity or whole-body insulin sensitivity by either M value or M/I (included in Table 2 for reference).…”
Section: Ihl and Insulin Sensitivitysupporting
confidence: 63%
“…The full methodology has been described previously 26 . In brief, a two‐step hyperinsulinaemic‐euglycaemic clamp with a stable glucose isotope infusion was used to assess whole‐body and hepatic‐specific insulin sensitivity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metabolically favourable qualities of sSAT exist due to its lower pro-inflammatory secretions as well as its ability to store excess triglycerides efficiently, thereby preventing the spill-over of free fatty acids into ectopic fat depots [ 9 ]. Our suggestion of a protective role of sSAT during obesity in BWA men may explain the lower levels of VAT and intrahepatic fat that is typically reported in black populations [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 62%